Criação de um banco de dados do padrão sucessório das principais espécies de Dípteros de importância forense no estado do Mato Grosso, através de identificação molecular (DNA Barcode) - Dantas, Elisangela Santana de Oliveira [UNESP] (2014)
The criminal Skill works with a large number of situations within their areas of expertise. Within this diversity of studies is forensic entomology, which uses insects allied to justice to answer questions everyday. as discovering routes trafficking, mistreatment of people and PMI (postmortem interval), which is the main focus of this work. When there are cases in which people are involved, the faster the identification thereof, will be best for the family suffering from their loss. For this to occur it is necessary to combine several areas of Criminal Skill for this identification to consolidate and entomology are included in one of these areas. Correct identification of insect species found in the body is a tool that aids in this search for truth. However, there is great difficulty in the identification of immature insects and this slows down the work skill. The DNA bar code has been successfully used in the identification of insects. The correct species identification is important for the conservation of biodiversity and quantification. Thus this work aims to generate a database of sequences of DNA barcode. The gene used as a DNA barcode is the mitochondrial gene Cytochrome C Oxidase 1 (COI). Validation of the COI gene of the DNA bar as taxonomic tool for identification of species of Diptera phoresis of interest, code obtained a satisfactory outcome of the identified species. The DNA bar code interacts between the Classical and Molecular taxonomy for accurate species identification. The results of this study showed that as taxonomic tool, the DNA barcode can be used for molecular identification of insects of forensic interest